O programa residência pedagógica e a formação de professores em experiências de alfabetização e letramento - CARDOSO, Dilvana Pereira (2023)
This study is involved in the theme Teacher Training, Literacy and Literacy around the Pedagogical Residency Program (PRP/CAPES), whose main objective is to describe and analyze the contributions of the PRP in the initial training process in the Pedagogy Course at the Federal University of the State do ParáUFPA/Abaetetuba Campus. The PRP, through the subproject aimed at training literacy teachers with an integrative theoretical basis of literacy and literacy linked to linguistic knowledge, in an interdisciplinary dimension, attributes broader training perspectives both to undergraduates in the Pedagogy course and in the Languages course. At the methodological level, we used a bibliographical study, subsidized by a qualitative exploratory research from the observations and experiences lived in the PRP. Thus, we observe a series of didactic-pedagogical procedures developed by the professors, as well as the attitudes of the students during the development of the activities. The results indicate that, even in the face of a Covid-19 pandemic scenario, residents were able to create a new form of action and participation in the literacy process; just as the importance of the lived experience was extremely relevant for them to come to exercise teaching practices with the use, including, of technological tools at this level of education.